Double-edged sword effect of anticoagulant in COVID-19 infection - May Honey Ohn; Jun Rong Ng; Khin Maung Ohn; Ng Pey Luen (BMJ Publishing Group, 2021)
Coagulation predominant-type coagulopathy such as microthrombosis and macrothrombosis is a well-known recognised complication found in COVID-19 infected critically ill patients. In the context of high incidence of thrombotic events in patients with COVID-19, supplementation with anticoagulant therapy has been routinely recommended and shown to reduce mortality. However, the recommended type, dose, duration and timing of anticoagulant has not been determined yet. Spontaneous retroperitoneal haematoma secondary to anticoagulant therapy is one of the well-known but self-limiting conditions. We report a 51-year-old COVID-19 positive woman, who was taking intermediate-intensity heparin therapy for venous thromboembolism prophylaxis and died from complication of retroperitoneal bleeding. Further studies are needed to verify the risk–benefit ratio of anticoagulant therapy in patients with COVID-19. Although anticoagulant deems appropriate to use in patients with COVID-19, clinicians should be cautious about major bleeding complication such as retroperitoneal haemorrhage even when full therapeutic dosage is not used.